A survey of remote-sensing big data - Liu, Peng (Frontiers in Environmental Science, 2015)
We have entered an era of big data. It is popular to refer to the three Vs when characterizing big data: remarkable growths in the volume, velocity and variety of data. However, this statement is too general. Remote-sensing big data has several concrete and special characteristics: multi-source, multi-scale, high-dimensional, dynamic-state, isomer, and non-linear characteristics. This survey explains these characteristics in detail. Furthermore, according to whether the characteristics are closely related to the instruments or methods of data acquisition, we points out that the dynamic-state, multi-scale and non-linear characteristics are intrinsic characteristics of remote-sensing big data while the multi-source, high-dimensional and isomer characteristics are extrinsic characteristics of remote- sensing big data. In addition, we briefly review promising techniques and applications of remote-sensing big data.